Search for Higgs boson decays to a photon and a Z boson in pp collisions at s√=7 and 8 TeV with the ATLAS detector - Aad, G. (2013)
A search is reported for a neutral Higgs boson in the decay channel H → Z γ, Z → ℓ + ℓ − ( ℓ = e, µ), using 4.5 fb − 1 of pp collisions at √ s = 7 TeV and 20.3 fb − 1 of pp collisions at √ s = 8 TeV, recorded by the ATLAS detector at the CERN Large Hadron Collider. The observed distribution of the invariant mass of the three final-state particles, mℓℓγ, is consistent with the Standard Model hypothesis in the investigated mass range of 120–150 GeV. For a Higgs boson with a mass of 125.5 GeV, the observed upper limit at the 95% confidence level is 11 times the Standard Model expectation. Upper limits are set on the cross section times branching ratio of a neutral Higgs boson with mass in the range 120–150 GeV between 0.13 and 0.5 pb for √ s = 8 TeV at 95% confidence level.